A research on the improvement of small and medium-sized city in early modern China (1895—1927) -- Taking Southern Jiangsu as an example - Xiaoqiang, Fu; Baihao, Li (International Planning History Society Proceedings, 2016)
In 1895, the failure of Sino-Japanese prompted the trend of comprehensive and systematic study of western pattern in China. In urban planning and construction, urban reform movement sprang up slowly, which aimed at renovating and reconstructing the traditional cities into modern cities similar to the concessions. During the movement, Chinese traditional city initiated a process of modern urban planning for its modernization. Meanwhile, the traditional planning morphology and system started to disintegrate, on the contrary, western form and technology had become the paradigm. Therefore, the improvement of existing cities had become the prototype of urban planning of early modern China. Currently, researches of the movement mainly concentrate on large cities, concessions, railway hub cities and some special cities resembling those. However, the systematic research about the large number of traditional small and medium-sized cities is still blank, up to now. This paper takes the improvement constructions of small and medium-sized cities in Southern region of Jiangsu Province as the research object. First of all, the criteria of small and medium-sized cities are based on the administrative levels of general office and cities at the county level. Secondly, the suitability of taking the Southern Jiangsu as the research object. The southern area of Jiangsu province called Southern Jiangsu for short, was the most economically developed region in Jiangsu, and also one of the most economically developed and the highest urbanization regions in China. As the most developed agricultural areas in ancient China, Southern Jiangsu formed a large number of traditional small and medium-sized cities. In early modern times, with the help of the Shanghai economic radiation, geographical advantage and powerful economic foundation, Southern Jiangsu became an important birthplace of Chinese national industry. Furthermore, the strong business atmosphere promoted the widespread urban improvement practices, which were incomparable of other regions. Meanwhile, the demonstration of Shanghai, Zhenjiang, Suzhou and other port cities became the improvement pattern of small and medium-sized city in Southern Jiangsu. This paper analyzes the reform movement of the small and medium-sized cities in Southern Jiangsu (1895-1927), including the subjects, objects, laws, technologies and the influence factors of politic and society ,etc. At last, this paper reveals the formation mechanism and characteristics of urban improvement movement in early modern China. According to the paper, the improvement of small-medium city was a kind of gestation of the local city planning culture in early modern China，with a fusion of introduction and endophytism.